The values of leadership in badminton game - Amat Komari; Sugiyono Sugiyono; Siswantoyo Siswantoyo; Agus Susworo Dwi Marhaendro; Suhadi Suhadi; Muhamad Nanang Solikhin; Yanuar Rachman Sadewa (Jurnal Cakrawala Pendidikan, 2023)
The values in sport settings have long been discussed in the literature, including the ones in the context of badminton. Despite there have been many leadership values in the literature, there is no explicit leadership value coming from research in badminton. Therefore, the purpose of the current study was to investigate the values of leadership being learned from the badminton game and develop value products through Research and Development. The research method used was a mixed method. Participants of the study included 7 former badminton players having leadership positions and 122 students in physical education teacher education program. Data were collected through in-depth interviews and survey. The results of these interviews were then interpreted, reduced, and given codes so that the values of leadership in badminton were obtained converging. The results of the research on leadership values in badminton games included (1) knowing the boundaries of territory (2) realizing the limits of authority (3) working together (4) obeying rules (5) keeping secrets (6) depth of knowledge (7) elegant decisions (8) obeying superiors (9) act with heart. The value products have been implemented and measured their effectiveness. It concludes that badminton provides opportunities to learn and develop leadership competencies. The value products are effective as a model for teaching leadership through badminton.